The Effect of Gene Variants on Levonorgestrel Pharmacokinetics When Combined With Antiretroviral Therapy Containing Efavirenz or Nevirapine. Issue 3 (30th May 2017) - Neary, M; Lamorde, M; Olagunju, A; Darin, KM; Merry, C; Byakika‐Kibwika, P; Back, DJ; Siccardi, M; Owen, A; Scarsi, KK
Abstract : Reduced levonorgestrel concentrations from the levonorgestrel contraceptive implant was previously seen when given concomitantly with efavirenz. We sought to assess whether single nucleotide polymorphisms (SNPs) in genes involved in efavirenz and nevirapine metabolism were linked to these changes in levonorgestrel concentration. SNPs in CYP2B6, CYP2A6, NR1I2, and NR1I3 were analyzed. Associations of participant demographics and genotype with levonorgestrel pharmacokinetics were evaluated in HIV‐positive women using the levonorgestrel implant plus efavirenz‐ or nevirapine‐based antiretroviral therapy (ART), in comparison to ART‐naïve women using multivariate linear regression. Efavirenz group: CYP2B6 516G>T was associated with lower levonorgestrel log10 Cmax and log10 AUC. CYP2B6 15582C>T was associated with lower log10 AUC. Nevirapine group: CYP2B6 516G>T was associated with higher log10 Cmax and lower log10 Cmin . Pharmacogenetic variations influenced subdermal levonorgestrel pharmacokinetics in HIV‐positive women, indicating that the magnitude of the interaction with non‐nucleoside reverse transcriptase inhibitors (NNRTIs) is influenced by host genetics.